Witwatersrand composite paleoplacers - V. A. Stepanov (Известия высших учебных заведений: Геология и разведка)
Background. The Witwatersrand gold province located in South Africa is the richest in the world. The Witwatersrand deposits are composite, where osmirids and diamonds are mined along with gold, silver and uranium. The genesis of the Witwatersrand deposits is controversial. Most local geologists support the hypothesis of the presence of paleoplacer deposits with subsequent metamorphic transformation of ore-bearing conglomerates. In addition, there are aeolian, hydrothermal-sedimentary, hydrothermal-sedimentary-metamorphic and magmatic models of ore formation.Aim. To establish the genesis of the Witwatersrand deposits.Materials and methods. Analysis of published literature and factual data.Results. Osmirids and diamonds are mined along with gold, silver and uranium from the composite Witwatersrand deposits. Such a set of useful components is not known in any of the deposits of magmatic or hydrothermal genesis. Considering the confinement of useful components to conglomerates, the detrital nature of most of the gold grains and the presence of various accompanying minerals in the heavy fraction, characteristic of igneous rocks of felsic, basic and ultrabasic composition, the hypothesis of the primary alluvial nature of the deposits of the Witwatersrand province looks the most reasonable.Conclusions. The factual material indicates an alluvial origin of the Witwatersrand deposits with subsequent metamorphic transformation of ore-bearing reefs. The primary alluvial formation of ore-bearing conglomerates is indicated by the confinement of gold and uranium to channel facies with a tendency to accumulate in the basal horizons of the reefs, the presence of rounded gold particles bearing the traces of transportation in alluvial flows, as well as a set of minerals in the heavy fraction of concentrate, characteristic of placers.